Gold nanoparticles on zinc oxide imaged by electron microscopy - Sónia Carabineiro (2014)
ZnO materials with different micro/nanoscale morphologies (needle-like, rods, flower-like and spheroidal) were preparedby different techniques. Gold was loaded (1% wt.) on the ZnO supports through a double impregnation method. Themorphology of the ZnO and Au/ZnO materials was analyzed by scanning electron microscopy (SEM) and energydispersiveX-ray spectroscopy (EDS). Scanning transmission electron microscopy (STEM) and a high-angle annular darkfield(HAADF) detector were used to detect the gold anoparticles. High-resolution transmission electron microscopy (HRTEM) of Au/ZnO was also performed. As gold is only catalytically active in the form of nanoparticles well dispersed on the support, it is very important to use electron microscopy methods that enable the determination of size, morphology,crystallinity and chemistry of nanoscale gold.